Analisis Pengaruh Asset Growth, Liquidity, Dan Asset Size Terhadap Kinerja Keuangan - Ayunda Putri Nilasari; Retnosari Retnosari (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2020)
Increase or decrease in assets is common in a company. The increase in assets should be followed by increased financial performance. That is because assets are an important element of the company. Another important element is company liquidity. The existence of a research gap regarding factors that affect financial performance is interesting to be examined again. This study aims to determine the effect of asset growth, liquidity and asset size on financial performance. The research method used in this research is multiple linear regression analysis. The population in this study are all LQ 45 companies listed on the Indonesia Stock Exchange in 2016-2020. Sampling uses a purposive sampling technique with criteria for companies that enter LQ 45 and never leave the LQ 45 index during the study period. The research period starts from the release of the LQ45 index in February 2016 to the LQ45 index in January 2020. From these criteria obtained 124 companies. The analysis shows that partially asset growth, liquidity, and asset size significantly influence financial performance. Simultaneously, asset growth, liquidity and asset size significantly influence financial performance.